The effect of a passive trunk exoskeleton on metabolic costs during lifting and walking. Issue 7 (3rd July 2019) - Baltrusch, S. J.; van Dieën, J. H.; Bruijn, S. M.; Koopman, A. S.; van Bennekom, C. A. M.; Houdijk, H.
Abstract: The objective of this study was to assess how wearing a passive trunk exoskeleton affects metabolic costs, movement strategy and muscle activation during repetitive lifting and walking. We measured energy expenditure, kinematics and muscle activity in 11 healthy men during 5 min of repetitive lifting and 5 min of walking with and without exoskeleton. Wearing the exoskeleton during lifting, metabolic costs decreased as much as 17%. In conjunction, participants tended to move through a smaller range of motion, reducing mechanical work generation. Walking with the exoskeleton, metabolic costs increased up to 17%. Participants walked somewhat slower with shortened steps while abdominal muscle activity slightly increased when wearing the exoskeleton. Wearing an exoskeleton during lifting decreased metabolic costs and hence may reduce the development of fatigue and low back pain risk. During walking metabolic costs increased, stressing the need for a device that allows disengagement of support depending on activities performed. Practitioner summary: Physiological strain is an important risk factor for low back pain. We observed that an exoskeleton reduced metabolic costs during lifting, but had an opposite effect while walking. Therefore, exoskeletons may be of benefit for lifting by decreasing physiological strain but should allow disengagement of support when switching between tasks. Abbreviations: COM: centre of mass; EMG: electromyography; LBP: low back pain; MVC: maximum voluntary isometric contraction; NIOSH: National Institute for Occupational Safety and Health; PLAD: personal lift augmentation device; PWS: preferred walking speed without exoskeleton; PWSX: preferred walking speed with exoskeleton; ROM: range of motion; RER: respiratory exchange ratio; V ̇O2max: maximum rate of oxygen consumption